Some aspects of the quenching of single-particle strength in atomic nuclei - Macchiavelli, Augusto O.; Paschalis, Stefanos; Petri, Marina (Frontiers in Physics, 2025)
In this article, we discuss some aspects of the quenching of the single-particle strength with emphasis on the isospin dependence of long- and short-range correlations. A phenomenological analysis that connects recent Jefferson Laboratory studies with data on spectroscopic factors, is contrasted with the results of the Dispersive Optical Model approach. We consider some consequences of the model on the nature of the dressed nucleons in the nuclear medium, their effective masses, as well as other aspects of nuclear structure such as charge radii, effective charges, and spin-spin correlations. Qualitative estimates indicate that short-range correlations must play a significant role on those aspects. Despite the fact that our conclusions are perhaps speculative at this stage, we trust that the results will stimulate further experimental and theoretical work, specifically on exotic nuclei far from stability.